The Effect of Realia Strategy and Self-Regulated Learning (SRl) Tto The English Learning Result - Nuke Lismarini; Mustaji; Djoko Adi Walujo (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2019)
The focus of this study was to determine whether any interactions between Realia Strategy and Self-Regulated Learning (SRL) to the English learning result of the seventh grade students in SMPN 1 & 2 Dlanggu Mojokerto. The research approach used in this study was a quantitative. The research population was the seventh grade students in SMPN 1 & 2 Dlanggu Mojokerto. The number of the respondents who took part in this research was 128. The findings revealed that the majority of the respondents were the seventh grade students and both genders were almost equally represented in the sample. Test and questionnaire were conducted with 128 respondents using a prepared structured test and questionnaire schedule. The test and questionnaire was managed for easy analysis and analysed using SPSS computer program. Based on the data analysis and hypothesis verification, it can be concluded that there are any differences of the English learning result between a group of students who is given a treatment using Realia Strategy and a group of students who is given a treatment using Display Strategy, between a group of students who has High Self-Regulated Learning (SRL) and Low Self-Regulated Learning (SRL), and there are any interactions between Realia Strategy and Self-Regulated Learning (SRL) to the English learning result of the seventh grade students in SMPN 1 & 2 Dlanggu Mojokerto. It can be said that there is significant interaction of Realia Strategy and Self-Regulated Learning (SRL) to the English Learning Result of the Seventh Grade Students in SMPN 1& 2 Dlanggu Mojokerto. According to the findings of the research, Realia strategy and Self-Regulated Learning (SRL) are able to be implemented in classroom to improve students’ English learning result.